"Beasts in Human Form": How Dangerous Speech Harms - Marques, Teresa (Araucaria, 2019)
Recent years have seen an upsurge of inflammatory speech around the world. Understanding the mechanisms that correlate speech with violence is a necessary step to explore the most effective forms of counterspeech. This paper starts with a review of the features of dangerous speech and ideology, as formulated by Jonathan Maynard and Susan Benesch. It then offers a conceptual framework to analyze some of the underlying linguistic mechanisms at play: derogatory language, code words, figleaves, and meaning perversions. It gives a hypothesis for assessing the moral responsibility of interlocutors in dangerous speech situations. The last section applies this framework to the case of demagogic discourse by Catalan nationalists. The framework offered explains how public discourse in Catalonia has harmed social relations and institutions, and is an obstacle to rational resolutions to the political situation.